MO951ASSESSMENT OF HEALTH-RELATED QUALITY OF LIFE (HRQOL) IN A GREEK COHORT OF KIDNEY TRANSPLANT RECIPIENTS WITH THE KIDNEY TRANSPLANT QUESTIONNAIRE (KTQ-25). (29th May 2021) - Koutlas, Vasileios; Tzalavra, Eirini; Tatsis, Vasileios; Duni, Anila; Pappas, Haralambos; Priska, Silvia; Mitsis, Michalis; Ntounousi, Evangelia
Abstract: Background and Aims: Kidney transplantation is recognized as the treatment of choice for patients with End Stage Kidney Disease (ESKD). Improvement in short term patient and graft survival of kidney transplant recipients (KTRs), has shifted interest to the long-term outcomes and Health-Related Quality of Life (HRQoL) estimation is closely related. Thus, reliable evaluation of HRQoL with disease specific questionnaires is of great importance. The aim of this study was to assess the HRQoL in adult KTRs of our Transplant Unit with Kidney Transplant Questionnaire 25 (KTQ-25) and the 36-item Short Form Health Survey (SF-36). Method: The Greek version of the recently translated and adapted by our team disease specific instrument KTQ-25 and the Greek SF-36 were administered in KTRs during their routine visit in the transplant outpatient clinic. Patients who met the eligibility criteria (time since transplant≥1 year, aged≥18 year old, functioning transplant) were included after providing written informed consent. Results: A total of 84 KTRs (59 males; mean age 53.45±10.72; mean e-GFR 47.69±15.07; average time since transplantation 55.68±48.26 months) completed the two questionnaires. The scores in each dimension of KTQ-25 were: Physical Symptoms 3.98±1.60, Fatigue 5.30±1.36, Uncertainty/Fear 5.16±1.33, Appearance 6.31±0.94, Emotions 5.03±1.07 and Total Score 5.20±0.87. The mean SF-36 Physical Component Score (PCS) and Mental Component Score (MCS) scores were 47.98±8.70 and 46.94±9.70 respectively. Fatigue (p=0.009), Uncertainty/Fear (p=0.008) and Total Score (p<0.001) were better in male sex. Physical Symptoms (p=0.013) was better in KTRs with children than those with no children. There was positive correlation of e-GFR with Fatigue (p 0.002), Uncertainty/Fear (p=0.034) and Total Score (p=0.017). Hgb was positive correlated with Fatigue (p<0.001), Uncertainty/Fear (p<0.001), Emotions (p=0.031) and Total Score (p<0.001). KTRs who were receiving EPO for anemia had worse scores in all dimension of KTQ-25 (Physical Symptoms p=0.001; Fatigue p=0.001; Uncertainty/Fear p=0.021; Emotions p=0.010; Total Score p=0.002) except Appearance. Appearance was negative correlated with Weight (p=0.001) and BMI (p=0.001). Total number of daily taken pills was also significantly negative correlated with Fatigue (p=0.006) and Total Score (p=0.007). No differences found between different immunosuppressive therapies. Conclusion: In our cohort of Greek adults KTRs maximum KTQ-25 score was obtained in Appearance dimension and the minimum in Physical Symptoms dimension. Fatigue, Uncertainty/Fear dimensions and Total Score were better for male sex and for KTRs with higher e-GFR and Hgb levels. Physical Symptoms score was better only for KTRs having children. Overweight and high BMI negatively affected A dimension. This is the first study to use a specific-disease tool for evaluating HRQoL in Greek KTRs and among our significant results is that better graft function is significantly correlated with better HRQoL.